Effect of KI on SDF Treated Cavities - Ola Mohamed Ismail Sakr; Mashail Abdullah Alsaikhan (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Dental caries is the most frequent chronic disease worldwide. However, Dental caries can be prevented or arrested. Recently interest in the use of silver diamine fluoride (SDF) has been growing. (SDF) is a solution containing ionic silver, fluoride, and ammonia that arrests the progress of carious lesions and prevents the development of future caries. In Vitro studies demonstrated that SDF increases the pH of biofilm, reduces dentin demineralization, and has antimicrobial action against cariogenic bacteria. But it produces a lesion darker (brown to black) than the original, which is the major criticism of the material. To counter the staining, many studies have tested SDF treatment immediately followed with a saturated solution of potassium iodide.Material and Methods: A vitro study done in Qassim University, with sample of 30 extracted premolars, divided into 3 groups, (Group A): received silver diamine fluoride, followed by application of Potassium iodide. (Group B): cavity preparation 1 mm in enamel then Received silver diamine fluoride followed by application of Potassium Iodide. And (Group C): cavity preparation 1 mm beyond dentoenamel junction then Received silver diamine fluoride followed by application of Potassium Iodide.Result: There was a statistically significant differences between three groups on color measurement p= (0.020), this means that the prevalence for group c-based change color teeth compared to group A and B.Conclusion: SDF + KI treatment showed a low intensity staining in superficial and deep cavities. The intensity of staining decreased significantly in dentin prepared cavities.